2012
DOI: 10.5455/2319-2003.ijbcp003412
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of antihypertensive drugs in the management of pregnancy-induced hypertension

Abstract: Background: Pregnancy-induced hypertension is associated with various adverse fetal and maternal outcomes. The use of anti-hypertensive drugs in pregnancy is controversial. We conducted a prospective study to evaluate the comparative effectiveness and safety of nifedipine, methyldopa and labetalol monotherapy in patients with pregnancy-induced hypertension. Methods: A total of 60 pregnant women with blood pressure of 140/90 mm Hg or more with ≥1+ proteinuria between 20 and 38 weeks of gestation were rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…Our review also found that women consuming a balanced diet, including enough energy based on their individual requirements, had lower BP, paralleling current lifestyle recommendations for individuals with high BP (National Institutes of Health 2003).The effect size of 1-3 mmHg was very small compared with using antihypertensive agents (Patel et al 2012). However, the effect was evident in normotensive rather than hypertensive women.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Our review also found that women consuming a balanced diet, including enough energy based on their individual requirements, had lower BP, paralleling current lifestyle recommendations for individuals with high BP (National Institutes of Health 2003).The effect size of 1-3 mmHg was very small compared with using antihypertensive agents (Patel et al 2012). However, the effect was evident in normotensive rather than hypertensive women.…”
Section: Discussionsupporting
confidence: 75%
“…The effect size of 1–3 mmHg was very small compared with using antihypertensive agents (Patel et al . ). However, the effect was evident in normotensive rather than hypertensive women.…”
Section: Discussionmentioning
confidence: 97%
“…7,8 In contrary to this study, Patel NK et al, have proved that labetalol has better efficacy than nifedipine in nonsevere preeclampsia. 9 In the same study by Bharathi et al both the drugs had side effects but they were higher in nifedipine group. Similar to our study the most common side effect with nifedipine was headache.…”
Section: Discussionmentioning
confidence: 86%
“…15 In the present study, only one (3.33%) patient developed severe hypertension in labetalol group, while 2 (6.66%) patients in the methyldopa group developed severe hypertension, but there was no statistically significant difference between two groups (p value=1). In the present study, none of the patients developed other complications like eclampsia, abruption and severe pre-eclampsia.…”
Section: Discussionmentioning
confidence: 52%